Research of natural wood combustion and charring processes - Mačiulaitis, Romualdas; Jefimovas, Andrejus; Zdanevičius, Povilas (Journal of Civil Engineering and Management, 2012)
Wood is a material widely used for construction purposes and – in some cases – it is the main element of building structures. In comparison with other materials, wood has a number of advantages, such as lightness, strength, resistance to impacts and vibration, simplicity in terms of processing and etc. However, one of the largest drawbacks of wood is flammability. Charring of wooden structures is the most apparent feature of combustion in case of fire in wooden buildings or buildings made of wooden structures. This property is important in identifying causes of fire; therefore it is necessary to relate charring of wooden structures with certain significant effects of fire, such as its duration or temperature. The article addresses the wood characteristics that impact on combustion and charring. It describes test methods and properties of wood samples under research. Research of charring rate of natural softwood and hardwood as a function of heating time, and regressive analysis of data were carried out. Empiric equations were derived. The calorific value of carbon residue resulting in different temperatures was determined in accordance with LST EN ISO 1716. Thermographic research of oak and pine wood was carried out in different gaseous environments. The research results were summarised in the form of conclusions.